Occupational Therapy in Primary Care: Structures and Processes that Support Integration - Brenda Koverman; Lydia Royeen; Mary Stoykov (Scholarworks @ WMU, 2017)
Few studies have outlined the processes and structures needed to develop and integrate occupational therapy into a primary care provider's office setting. This paper focuses on implementation of the clinic model of occupational therapy in primary care and is intended to address the deficiencies in current literature, including detailed program development steps. Barriers identified in the 8-week pilot program and the successful development of a reimbursable occupational therapy service in primary care will be discussed. The results of the implementation of occupational therapy in primary care are positive. The providers have accepted and embraced the distinct value of occupational therapy in this setting. Occupational therapy in the primary care setting is an emerging area of practice and further research is needed to measure the impact of interventions in this setting and the relationship to outcomes.